1998
DOI: 10.1038/bjc.1998.37
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of plasma and tissue levels of ZD1694 (Tomudex), a highly polyglutamatable quinazoline thymidylate synthase inhibitor, in preclinical models

Abstract: Summary ZD1 694 (Tomudex, raltitrexed) is a specific quinazoline antifolate thymidylate synthase inhibitor that relies on polyglutamation for high potency. Antibodies to ZD1694 have been used to establish a sensitive radioimmunoassay as an alternative to high-performance liquid chromatography (HPLC). The radioimmunoassay is reproducible, accurate and provides a means of determining low levels of ZD1694 in plasma (< 1 nM). By virtue of the high cross-reactivity of the antibodies with polyglutamated forms of ZD1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Triexponential elimination of raltitrexed and a prolonged terminal elimination phase has also been found in mice and dogs [3], but no terminal half-life was calculated. The pharmacokinetic parameters obtained in nonhuman primates in this study are comparable to those reported in adult patients with colorectal cancer who received raltitrexed as a 15-min bolus infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Triexponential elimination of raltitrexed and a prolonged terminal elimination phase has also been found in mice and dogs [3], but no terminal half-life was calculated. The pharmacokinetic parameters obtained in nonhuman primates in this study are comparable to those reported in adult patients with colorectal cancer who received raltitrexed as a 15-min bolus infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were collected over 24–72 h in the Phase I studies and up to 29 days in the studies where the radiolabelled drug was administered and where the effect of renal function was investigated. Raltitrexed plasma concentrations were determined using a sensitive radioimmunoassay which uses sheep antiserum raised against raltitrexed [6, 22]. Assay performance was monitored using control samples.…”
Section: Methodsmentioning
confidence: 99%
“…Assay performance was monitored using control samples. The intra‐ and interassay coefficient of variation for plasma measurements was 10.7% and 12.9%, respectively, and the reported lower limit of detection of the assay was 0.2 ng ml −1 [22].…”
Section: Methodsmentioning
confidence: 99%
“…Raltitrexed is transported into cells by the reduced folate carrier, metabolized to polyglutamated species, and retained intracellularly, resulting in prolonged TS inhibition [40].…”
Section: Raltitrexedmentioning
confidence: 99%